2012
DOI: 10.4236/health.2012.43018
|View full text |Cite
|
Sign up to set email alerts
|

Risks of iron deficiency among vegetarian college women

Abstract: Iron deficiency anemia is the most common nutritional deficiency disease worldwide and poses a major threat in women of child-bearing age and those who follow a vegetarian diet. The objective of this study was to ascertain whether differences exist in iron status markers between female university students following a vegetarian and non-vegetarian diet. This study took a cross sectional analysis of 39 female students at California Polytechnic State University (Cal Poly State University) in San Luis Obispo, CA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…This study examined the iron status of Spanish vegetarians for the first time. The results reveal that IDA prevalence was low, consistent with previous reports in vegetarians from developed countries [13,24,25]. In order to detect iron deficiency before the appearance of IDA, sTfR in addition to the classical iron markers was determined.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study examined the iron status of Spanish vegetarians for the first time. The results reveal that IDA prevalence was low, consistent with previous reports in vegetarians from developed countries [13,24,25]. In order to detect iron deficiency before the appearance of IDA, sTfR in addition to the classical iron markers was determined.…”
Section: Discussionsupporting
confidence: 88%
“…While non-menstruating women and men lose approximately 1 mg of iron daily, menstruating women lose 10 to 42 extra mg per menstrual cycle [6]. This loss leads to lower iron status in women of reproductive age than in men independently of their diet [13]. Menstruation could be of special interest in vegetarian women, as previous reports suggest that they present menstrual alterations [14].…”
Section: Introductionmentioning
confidence: 99%
“…The higher consumption of MUFA and PUFA corroborates previous studies (Hawk, Englehardt & Small, 2012;Kristensen et al, 2015) as well as the higher ratio of unsaturated to saturated fatty acids (Majewska et al, 2016) and fiber intake (Vinagre, Vinagre, Pozzi, Zacari & Maranhao, 2014). However, no influence of this dietary pattern on plasma concentrations of total cholesterol were noted between the groups, contradicting studies that evidence this tendency when food of animal origin is restricted (Santos et al, 2013;Vinagre et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Two studies have found similar values (Hawk et al, 2012;Shridhar et al, 2014). Shridhar et al (2014) found average intake of Fe between 25.5 mg and 22.4 mg in vegetarians and nonvegetarians, respectively, while in another study, this adjustment was found only in males, with an average intake of 18.5 mg (Hawk et al, 2012). Part of the discrepancy between the studies is due to food fortification, different evaluation methodologies and different consumption patterns.…”
Section: Discussionmentioning
confidence: 91%
“…National surveys within North America report rates of iron deficiency in women aged 20–49 years of 15% (United States) [ 1 ], 19%–27% (Mexico) [ 2 ], and 9% (Canada) [ 3 ]. An even higher rate of iron deficiency among female university students in the United States (30%–50%) [ 4 , 5 , 6 , 7 ] poses the risk of compromised academic achievement due to deficiency-related cognition impairment.…”
Section: Introductionmentioning
confidence: 99%